Mesenchymal Stromal Cells Protect Cancer Cells From ROS-induced Apoptosis and Enhance the Warburg Effect by Secreting STC1 - Ohkouchi, Shinya (Nature Publishing Group, 2012)
Previous studies have demonstrated that mesenchymal stromal cells (MSCs) enhance cell survival through upregulation and secretion of stanniocalcin-1 (STC1). This study shows that MSC-derived STC1 promotes survival of lung cancer cells by uncoupling oxidative phosphorylation, reducing intracellular reactive oxygen species (ROS), and shifting metabolism towards a more glycolytic metabolic profile. MSC-derived STC1 upregulated uncoupling protein 2 (UCP2) in injured A549 cells in an STC1-dependent manner. Knockdown of UCP2 reduced the ability of MSCs and recombinant STC1 (rSTC1) to reduce cell death in the A549 population. rSTC1-treated A549 cells displayed decreased levels of ROS, mitochondrial membrane potential (MMP), and increased lactate production, all of which were dependent on the upregulation of UCP2. Our data suggest that MSCs can promote cell survival by regulating mitochondrial respiration via STC1.